Cryopreservation and culture strategies for testicular tissue and cells in small and large animals - Vurchio, Valeria; Colombo, Martina; Pasquariello, Rolando; Luvoni, Gaia Cecilia (Frontiers in Veterinary Science, 2025)
The preservation of testicular tissue and male germ cells represents a cutting-edge technique for safeguarding fertility, especially when sperm collection is not possible, such as in prepubertal animals, those that die unexpectedly or that receive gonadotoxic therapies after cancer detection, and in adult males suffering from some pathology related to azoospermia. Current methods under investigation include the optimization of cryopreservation protocols, as well as the development of culture platforms to enable in vitro spermatogenesis (IVS). Although these approaches are still in the research and development phase, they have shown promising potential for male fertility preservation. Cryopreservation is a common method for long-term in vitro storage of tissue and cells, which enables the maintenance of reproductive capacity across different animal species and contributes to the creation of gene banks for endangered species. Spermatogenic cells from cryopreserved testicular tissue can be cultured in vitro and resume their functions after thawing, contributing to the preservation of fertility and genetic resources in both small and large animals. The main challenges of IVS include providing a suitable microenvironment that mimics the testicular niche to support the survival and development of all the cell types, as well as to achieve complete differentiation toward spermatozoa. Therefore, there is a great interest in developing methods to study IVS, both for basic research and clinical application. Given the importance of this topic, this review aims to provide an overview of recent advancements in the cryopreservation and culture of both testicular tissue and cells for preserving male fertility in large and small domestic animals.